A Study of the Relationship between Various NIFTY Sectoral İndices - Harshita Srivastava (International Journal of Advanced Science and Technology, 2020)
This paper provides a theoretical and empirical relationship between various sectoral indices on National Stock Exchange (NSE) and to the extent, they are related to each other. NIFTY is the index used by NSE to track the top 50 stocks (In terms of Market Capitalization). Various other sectoral indices were also introduced to have sector-wise trends. These indices are important as they help in gauging the market and helps in forecasting the trends. Investors can easily assess their risk and return based on the historical data provided by the indices. For our research, we have considered ten sectoral indices and studied their price movements for six years i.e. from January 2012 to April 2018 weekly. Correlation study and Regression model has been implemented to derive the relationship between the indices. The relationships are categorized into three parameters: Weak Correlation, Moderate Correlation and Strong Correlation. NIFTY Bank, NIFTY FMCG, NIFTY Financial Services, NIFTY Auto, NIFTY IT and NIFTY Media are Strongly correlated to most of the indices. NIFTY PSU Bank, NIFTY Pharma, NIFTY Metal and NIFTY Realty are Weakly Correlated to most of the indices.